1994
DOI: 10.2307/2154711
|View full text |Cite
|
Sign up to set email alerts
|

Graphs with the Circuit Cover Property

Abstract: Abstract. A circuit cover of an edge-weighted graph (G, p) is a multiset of circuits in G such that every edge e is contained in exactly p(e) circuits in the multiset. A nonnegative integer valued weight vector p is admissible if the total weight of any edge-cut is even, and no edge has more than half the total weight of any edge-cut containing it. A graph G has the circuit cover property if (G, p) has a circuit cover for every admissible weight vector p . We prove that a graph has the circuit cover property i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Edwards, Robertson, Sanders, Sey- Figure 1 mour and Thomas [RST97, RST15, RST14, SST,ESST14] have announced a proof that every bridgeless cubic P-minor-free graph is edge 3-colourable, which is equivalent to Tutte's conjecture in the cubic case. Alspach, Goddyn and Zhang [AGZ94] showed that a graph has the circuit cover property if and only if it has no P-minor. It is recognised that determining the structure of P-minor-free graphs is a key open problem in graph minor theory (see [DLM16,Mah98] for example).…”
Section: Petersen Minorsmentioning
confidence: 99%
“…Edwards, Robertson, Sanders, Sey- Figure 1 mour and Thomas [RST97, RST15, RST14, SST,ESST14] have announced a proof that every bridgeless cubic P-minor-free graph is edge 3-colourable, which is equivalent to Tutte's conjecture in the cubic case. Alspach, Goddyn and Zhang [AGZ94] showed that a graph has the circuit cover property if and only if it has no P-minor. It is recognised that determining the structure of P-minor-free graphs is a key open problem in graph minor theory (see [DLM16,Mah98] for example).…”
Section: Petersen Minorsmentioning
confidence: 99%